Nitrate - Nitrite Toxicosis in Animals and Their Cases in Indonesia - Yuningsih . (Indonesian Center for Animal Research and Development, 2000)
Nitrate is naturally present in the environment such as in plants, fertilized soil, and water. Toxicity of nitrate-nitrite in animals occurred when these animals consumed grasses or plants, which contained high level of nitrate. As a consequence nitrate is converted into lethal nitrite by the bacteria in the rumen. When nitrite is absorbed into the blood, haemoglobine (Hb) is converted by nitrite into methaemoglobine (MetHb) which reduces the oxygen uptake, if MetHb level reaches 20-30%. As a consequence the suffering animals show difficulty in breathing, the clinical sign develop when MetHb reaches 80-90%, causing the death of the animals and this MetHb levels result in brown discoloration of the blood, as a characteristic of nitrate-nitrite poisoning. Several cases of nitrate-nitrite poisoning were reported from Bogor, Bandung, Sukabumi, Jakarta, and Kupang in various animals from the year 1992 to 1997. It was reported that 6,250; 8,000; 2,000; 5,000 mg/kg nitrate and 10 mg/kg nitrite detected in the feed of zebra, dairy cattle, horse, sheep, and duck respectively. The grass containing high level of nitrate was probably due to over fertilized with organic and inorganic fertilizers. Key words : Poisoning, nitrate, nitrite, animals, grass, water